1997
DOI: 10.1038/bjc.1997.550
|View full text |Cite
|
Sign up to set email alerts
|

Lack of cyclin E immunoreactivity in non-malignant breast and association with proliferation in breast cancer

Abstract: Summary Cyclin E is a G, cyclin that is essential for the transition from G, to S phase in the cell cycle. Alterations to cyclin E expression or regulation could be important in tumorigenesis. Previous immunohistochemical and immunoblotting studies have investigated the expression of cyclin E in breast carcinomas. In this study, cyclin E has been investigated in a range of non-malignant and malignant breasj using immunohistochemistry. Normal and benign tissue from pre-and post-menopausal women (39 cases), non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 22 publications
3
25
1
2
Order By: Relevance
“…Likewise, Sakaguchi et al (20) noted a similar relationship with p53 and cyclin E positivity and poor prognosis in gastric carcinomas. The widespread expression of cyclin E in testicular germ cell tumors is in contrast to what has been noted in prostate and renal tumors but is similar to what has been seen in breast and cervical tumors (7,8,16,17,21). It should be noted that the examination of tumors that were chosen for their high percentage of embryonal carcinoma may introduce a selection bias for a more aggressive subset of germ cell tumors.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Likewise, Sakaguchi et al (20) noted a similar relationship with p53 and cyclin E positivity and poor prognosis in gastric carcinomas. The widespread expression of cyclin E in testicular germ cell tumors is in contrast to what has been noted in prostate and renal tumors but is similar to what has been seen in breast and cervical tumors (7,8,16,17,21). It should be noted that the examination of tumors that were chosen for their high percentage of embryonal carcinoma may introduce a selection bias for a more aggressive subset of germ cell tumors.…”
Section: Discussionsupporting
confidence: 50%
“…Expression of Ki-67 and Cyclin A in Germ Cell Tumors 21.9%) than the corresponding seminomas, although these numbers did not achieve statistical significance. The extent of cyclin A and Ki-67 expression in the tumors was strongly correlated.…”
Section: Tumor and Patient Profilesmentioning
confidence: 87%
“…In human ESCC tissues, increased expression level of cyclin D1 speeded the progress of ESCC and led to poor prognosis (32). It has been reported that overexpression of cyclin E was a general phenomenon associated with oncogenesis of breast cancer (33). Coupled with the above observations together; our results demonstrate that cyclins D1 and E may play an important role in development of ESCC cells.…”
Section: Discussionsupporting
confidence: 77%
“…5,[24][25][26][27] We showed that CCNE1 and CCNE2 were both associated with RFI in a univariate analysis, whereas CCNE2 was the only significant variable in the multivariate model. However, when CCNE2 was discarded, CCNE1 became significant.…”
Section: Discussionmentioning
confidence: 72%